2008
DOI: 10.1002/ptr.2645
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological studies of wogonin in experimental animals

Abstract: Wogonin, one active ingredient extract from the radix of Scutellaria baicalensis Georgi, is known to possess a broad spectrum of pharmacological, medicinal and therapeutic properties, especially the anticancer activity studied recently. However, no extensive safety studies have been conducted to date. In this paper, the acute and sub-chronic toxicity of the agent were determined using albino mice and Sprague-Dawley rats as animal models. Histopathological examination and viscera parameter investigation were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
3
23
0
Order By: Relevance
“…We have shown previously that wogonin enhances TRAIL-mediated apoptosis in leukemic but not in normal healthy lymphocytes (19). In particular, toxicological studies in experimental animals (mouse and dog) showed that up to 60 mg/kg/day wogonin had no organ toxicity when intravenously administered for 90 days (43,44). Therefore, wogonin may offer relative safety for long term therapies.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that wogonin enhances TRAIL-mediated apoptosis in leukemic but not in normal healthy lymphocytes (19). In particular, toxicological studies in experimental animals (mouse and dog) showed that up to 60 mg/kg/day wogonin had no organ toxicity when intravenously administered for 90 days (43,44). Therefore, wogonin may offer relative safety for long term therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies in experimental animals (rat and dog) showed that up to 60 mg/kg/day wogonin had no organ toxicity when intravenously administered for 90 days. 30, 31 Thus, wogonin may be an attractive new anti-cancer compound that offers relative safety for long term therapies.…”
Section: Discussionmentioning
confidence: 99%
“…After one week of STZ injection, mice were intraperitoneally administered either 10 mg/kg body weight of wogonin or vehicle control (20% dimethyl sulfoxide and 80% saline) once every three days for 8 weeks. Because the LD 50 of wogonin administered by intravenous injection in Sprague-Dawley rats was 286.15 mg/kg [18] , the doses or dose ranges used in this study were considered safe. At the end of wogonin treatment, the mice were euthanized, and adipose tissue and blood samples were harvested for experimentation.…”
Section: Antibodies and Reagentsmentioning
confidence: 99%